D-Stability Control Design for Algebraic Differential Systems with Application in Power Systems [Diseño de Controladores Para D-Estabilidad de Sistemas Algébrico Diferenciales Con Aplicación en Sistemas de Potencia] - Verdejo-Fredes, H; Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper focuses on the problem of D-stability control design for descriptor systems in algebraic differential representation. The aim is to design a control to ensure that all system eigenvalues in closed loop belongs to a given set in the complex plane. Sufficient LMI based conditions are proposed for both state and output feedback control. The proposed results are applied to a single-machine infinite-bus power system. © 2016 IEEE.